THE CORRELATION BETWEEN STUDENTS’ MOTIVATION IN LEARNING ENGLISH AND THEIR ENGLISH LEARNING ACHIEVEMENT - Novia Yulanda Putri; Dahnilsyah Dahnilsyah; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aimed to find out the correlation between students’ motivation in learning English and their English learning achievement of the first grade students of Madrasah Aliyah Khairul Ummah. The researcher used a descriptive quantitative method as the data approach. The sample of this research was the 57 students in class X IPA 1 and X IPS 2. The students’ motivation score was obtained from the questionnaire adapted from Gardner’s AMTB (Attitude/Motivation Test Battery) consist of 30 questions. Data on students’ English learning achievement acquire from the score of the final semester exam from the English teacher. As the result, the students’ motivation in learning English was at average level and students ‘ motivation in learning English is mostly intrinsic motivation. And for students’ English learning achievement is classified as enough level. Lastly, the correlation coefficient is 0.748, and it can be concluded that there is highly significant and positive correlation between students’ motivation in learning English and their English learning achievement at Madrasah Aliyah Khairul Ummah. With 0.5595 as the coefficient of determination, it can be deduced that the students’ motivation contributes about fifty-six percent to their English learning achievement, leaving the other fourty-four percent by the other factors.Key Words: Correlation, Students’ Motivation , English Learning Achievement